Electrochemical Behavior of a Glassy Carbon Electrode Chemically Modified with Nickel Pentacyanonitrosylferrate in Presence of Sulfur Compounds - Paim, Leonardo L. [UNESP]; Hammer, Peter [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Wiley-Blackwell, 2011)
The glassy carbon electrode was modified with a nickel pentacyanonitrosylferrate film by electrodeposition of Ni and subsequent derivatization with NaPCNF. The film was characterized by XPS and electrochemical methods. Cyclic voltammetry of the NiPCNF onto the GC shows a redox couple (Fe(III)/Fe(II)) with E(ol) of 538 mV (I(pa)/I(pc) around 1) and Delta E(p) of 93 mV in 0.5 mol L(-1) KNO(3), with a diffusion-controlled process. There was a decrease of anodic peak currents of the film in the presence of sulfide and 2-propanethiol due to a precipitation reaction on the film surface by nucleophilic attack.
Keywords: Mercaptan; Sulfide; Nickel pentacyanonitrosylferrate; Cyclic voltammetry; Square wave voltammetry